2020
DOI: 10.1155/2020/2939573
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ Experiences Using the Ekso Bionic Exoskeleton with Patients in a Neurological Rehabilitation Hospital: A Qualitative Study

Abstract: Use of bionic overground exoskeletons to assist with neurological rehabilitation is becoming increasingly prevalent and has important implications for physiotherapists and their patients. Yet, there is a paucity of research about the impact of integrating this technology on physiotherapists’ work. The purpose of this study was to explore how the training and implementation of using the Ekso robotic exoskeleton with patients affects physiotherapists’ work. An exploratory qualitative study of three physiotherapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 31 publications
2
80
0
Order By: Relevance
“…This study explored the perspectives of persons with stroke and their physiotherapists using in-depth semi-structured interviews following a single-use experience with a H2 exoskeleton. To date only one study using qualitative research methods has specifically investigated physiotherapist perspectives of exoskeleton use in persons with stroke [ 14 ]. Currently, no literature using qualitative research methods exists on the perspectives of persons with stroke with respect to exoskeleton technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study explored the perspectives of persons with stroke and their physiotherapists using in-depth semi-structured interviews following a single-use experience with a H2 exoskeleton. To date only one study using qualitative research methods has specifically investigated physiotherapist perspectives of exoskeleton use in persons with stroke [ 14 ]. Currently, no literature using qualitative research methods exists on the perspectives of persons with stroke with respect to exoskeleton technology.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a large body of evidence supporting the inclusion of end-user perspectives both in retail marketing and design of medical devices to ensure that products and devices meet end-user needs [ 12 ], end-user perspectives with respect to assistive technology, such as the exoskeleton for post-stroke gait rehabilitation, appears to be lacking [ 14 , 36 ]. The literature suggests that it is important that end-users have an actual exoskeleton experience as perceptions of, and experience with exoskeleton technology are potentially quite different [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fitting, donning and doffing), excessive cost, and the need for multiple therapists' assistance were described as resource-specific barriers to adoption into clinical practice. The importance of considering resource demands was also emphasised by Read et al [36], who identified a need for organisational support to offset the increased resource investment required to integrate the exoskeleton into physiotherapists' practice. It is critical, as exoskeleton technology advances, that resource demands match availability in clinical settings.…”
Section: Discussionmentioning
confidence: 99%